Purchasing IPOs with Commissions - Goldstein, Michael A.; Irvine, Paul; Puckett, Andy (Journal of Financial and Quantitative Analysis, 2011)
We find direct evidence that institutions increase round-trip stock trades, increase average commissions per share, and pay unusually high commissions on some trades in order to send abnormally high commissions to the lead underwriters of profitable initial public offerings (IPOs). These excess commission payments are a particularly effective way for transient investors to receive lucrative IPO allocations. Our results suggest that the underwriter’s concern for their long-term client relationships limits the payment-for-IPO practice. We estimate that abnormal commission payments are large for the most profitable issues, and that an additional $1 excess commission payment to the lead underwriter results in $2.21 in investor profits from allocated shares.